Final overall survival: fulvestrant 500 mg vs 250 mg in the randomized CONFIRM trial - Di Leo, Angelo; Jerusalem, Guy; Petruzelka, Lubos; Torres, Roberto; Bondarenko, Igor N; Khasanov, Rustem; Verhoeven, Didier; Pedrini, José L; Smirnova, Iya; Lichinitser, Mikhail R; Pendergrass, Kelly; Malorni, Luca; et al. (Journal of the National Cancer Institute, 2014)
BACKGROUND: At the time of the initial analysis of overall survival (OS) for the Comparison of Faslodex in Recurrent or Metastatic Breast Cancer (CONFIRM) randomized, double-blind, phase III trial, approximately 50% of patients had died. A final analysis of OS was subsequently planned for when 75% of patients had died. METHODS: Patients were randomly assigned 1:1 to fulvestrant 500 mg administered as two 5-mL intramuscular injections on days 0, 14, and 28 and every 28 (±3) days thereafter or fulvestrant 250 mg administered as two 5-mL intramuscular injections (one fulvestrant and one placebo [identical in appearance to study drug]) on days 0, 14 (two placebo injections only), and 28 and every 28 (±3) days thereafter. OS was analyzed using an unadjusted log-rank test. No adjustments were made for multiplicity. Serious adverse events (SAEs) and best response to subsequent therapy were also reported. All statistical tests were two-sided. RESULTS: In total, 736 women (median age = 61.0 years) were randomly assigned to fulvestrant 500 mg (n = 362) or 250 mg (n = 374). At the final survival analysis, 554 of 736 (75.3%) patients had died. Median OS was 26.4 months for fulvestrant 500 mg and 22.3 months for 250 mg (hazard ratio = 0.81; 95% confidence interval = 0.69-0.96; nominal P = .02). There were no clinically important differences in SAE profiles between the treatment groups; no clustering of SAEs could be detected in either treatment group. Type of first subsequent therapy and objective responses to first subsequent therapy were well balanced between the two treatment groups. CONCLUSIONS: In patients with locally advanced or metastatic estrogen receptor-positive breast cancer, fulvestrant 500 mg is associated with a 19% reduction in risk of death and a 4.1-month difference in median OS compared with fulvestrant 250 mg. Fulvestrant 500 mg was well tolerated, and no new safety concerns were identified.
Keywords: receptory pro estrogeny; Receptors, Estrogen; Antineoplastic Agents, Hormonal; Disease-Free Survival; Injections, Intramuscular; odds ratio; Drug Administration Schedule; Estrogen Receptor Modulators; Kaplan-Meier Estimate; vztah mezi dávkou a účinkem léčiva; Adult; Kaplanův-Meierův odhad; Aged; dospělí; Fulvestrant; nádory prsu; senioři; dvojitá slepá metoda; hormonální protinádorové látky; Estradiol; modulátory estrogenních receptorů; lidé; ženské pohlaví; Breast Neoplasms; Humans; fulvestrant; rozvrh dávkování léků; Odds Ratio; Double-Blind Method; Female; Dose-Response Relationship, Drug; lidé středního věku; injekce intramuskulární; přežití bez známek nemoci; estradiol; Middle Aged